Functional diversity of cover crop mixtures enhances biomass yield and weed suppression in a Mediterranean agroecosystem. (20th October 2019) - Ranaldo, M; Carlesi, S; Costanzo, A; Bàrberi, P
Summary: Functional diversity of cover crop mixtures is thought to improve biomass production and weed suppression, two key agroecosystem services in organic systems. To test this hypothesis, we selected eight cover crop species belonging to four functional groups: (i) vining growing large‐seeded legumes (field pea, common vetch), (ii) erect growing small‐seeded legumes (crimson clover, squarrosum clover), (iii) grasses (barley, oats) and (iv) Brassicaceae (radish, black mustard). Nine cover crop mixtures were designed to create a gradient of diversity in terms of number of species and number of functional groups. A control treatment and all monocrops were included in the trial. Regarding cover crop biomass, mixtures outyielded monocrops by an average of 37%. Both functional identity and composition (i.e. trait complementarity) influenced biomass production and weed suppression provided by cover crops. Regression analysis showed that increase in both species diversity and functional diversity in cover crop mixtures improved the provision of agroecosystem services. Results from this study show that complementarity of species functional traits in cover crop mixtures can be used as a strategy to ensure high biomass production and good weed suppression in changing agroecosystems.